El divorcio sin causal en Ecuador y el pleno desarrollo de los menores de edad - Machado Polo, Anderson Stefano (2025)
Marriage, as a legal institution, has evolved in response to sociocultural and regulatory changes. One of the most significant transformations deals with the no-fault divorce. As a legal procedure, no-fault divorce enables either spouse to dissolve the marital bond without providing justification. While this legal mechanism promotes individual autonomy, it also raises critical concerns regarding the protection of children's rights. In Ecuador, the absence of specific regulations addressing the implications of no-fault divorce may adversely affect the comprehensive development of children and adolescents particularly at their emotional, social and financial level. The current study aims to examine the impact of no-fault divorce on crucial areas such as child support, custody, and visitation rights. Utilizing descriptive and analytical methods, the research includes a normative review and a comparative analysis of Latin American legal frameworks. Additionally, interviews were conducted with judges from the Family, Women, Children, and Adolescents Judicial Unit in Riobamba - Ecuador. The findings indicate that although no-fault divorce simplifies legal proceedings and reduces conflict, reforms to the Ecuadorian legal system are necessary to safeguard the rights of minors during marital dissolution.